SPATIAL FRUITS PRODUCTION CONCENTRATION ACROSS DISTRICTS IN SLEMAN REGENCY - Fathan Aldi Rivai (Badan Perencanaan Pembangunan Daerah Kabupaten Sleman, 2025)
Population growth and changes in consumption patterns make fruits a strategic commodity in supporting food security and independence, as well as regional economic growth. Fruit production tends to be geographically concentrated, creating efficient production clusters. Indonesia has edaphic and climatic conditions that support the development of fruit production. Data-based development strategies and agglomeration analysis are needed to strengthen production clusters and realize sustainable regional development. This study aims to identify and analyze the spatial concentration of fruit production in Sleman Regency. The research materials consist of fruit production data in quintal units. Data analysis includes Locational Quotient (LQ), Localization Index (LI) and Specialization Index (SI). The units of analysis are sub-districts in Sleman Regency. The results showed that Sleman Regency produced 802,998 quintals of fruit in 2023, with salak as the commodity with the highest productivity, especially in Turi District. Minggir District showed the highest LQ value for mango, Cangkringan for durian, Sleman District for orange, Godean for banana, Ngemplak for papaya, Mlati for jackfruit and rambutan for Berbah. In interpreting the concentration of fruit production based on LI and specialization or diversification based on SI, it is necessary to confirm the data on fruit products of the analysis material. Generally, fruit production is concentrated in certain districts and most districts have unique fruit commodities. Fruit production in Sleman Regency shows a concentrated spatial pattern with superior commodity clusters, especially salak in Turi District. This pattern opens up opportunities for the development of regional-based fruit center areas. Strengthening production, mitigating pest attacks, and improving infrastructure are needed for efficient collection and distribution of harvest results.